CE ID genotype and leg power in Rugby Union players - Bell, W.; Colley, J. P.; Gwynne, J. R.; Glazier, P.; Evans, W. D.; Darlington, S. E. (The Journal of Sports Medicine and Physical Fitness, 2010)
AIM: The present study examined the hypothesis that there were no significant differences between forwards and backs in the elements of leg power between the ID and DD genotypes of the ACE (I/D) gene in developing young adult Rugby Union players. METHODS: Sixty-eight players were recruited to identify the distribution of genotypes between forwards and backs. Fifty-eight players were investigated for leg power. Forwards (n=28) comprised 15 ID and 13 DD genotypes, and backs (n=30) 19 ID and 11 DD genotypes. Leg power was measured on a force platform using a counter movement jump; the parameters of interest were peak and relative force, peak and relative power, displacement and velocity. The three-primer polymerase chain reaction was used to assay the region of interest for I and D variants of the ACE gene. The distribution of genotypes was determined by chi-square and comparisons between forwards and backs made using the independent t-test. RESULTS: No significant differences were identified in the distribution of genotypes between forwards and backs (c2=2.2, P=0.336). However, significant differences were identified between forwards and backs in a number of components of leg power. Backs had significantly larger values than forwards for relative force (1.50 vs. 1.30 Wt%, P=0.001) and relative power (27.1 vs. 24.3 W.kg-1, P=0.034) for the ID genotype, whereas backs had significantly larger values than forwards for displacement (0.42 vs. 0.38 m, P=0.049) and velocity (2.76 vs. 2.55 m/s, P=0.007) for the DD genotype. CONCLUSION: The characteristics of leg power identified will enhance the functional requirements of players according to playing position and commitment.